PENINGKATAN HASIL BELAJAR IPAS MENGGUNAKAN LEMBAR KERJA TEKA-TEKI SILANG PADA SISWA KELAS 4D - Adeulliah, Novie; Hiltrimartin, Cecil; Fauzie, Fauzie (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
Learning outcomes are still one of the obstacles in learning carried out in the classroom. Consistent improvement of learning outcomes is one of the indicators of success and learning, so that many efforts are made by teachers to achieve the desired goals. One of the efforts made is the use of crossword puzzle worksheets. Crossword puzzles are activities that help students understand the lesson by filling in the blank boxes in a descending and horizontal manner. The focus of this research is how teachers can plan, implement, and assess learning outcomes using crossword puzzle worksheets in grade IV students of SD Maitreyawira Palembang for the 2024/2025 school year. The method used in this study is descriptive in the form of class action research. The results showed that crossword puzzle worksheets were successfully used in IPAS lessons up to cycle II and developed during those cycles. The learning plan that took place in cycle I and cycle II increased by 19%. In addition, data in the first cycle showed an increase in learning outcomes from 15 complete students to 20 complete students in the second cycle. Based on this data, it can be concluded that crossword puzzle worksheets can improve students' learning outcomes in science lessons.